Comprehensive Computational Investigation of the Barton-Kellogg Reaction for Both Alkyl and Aryl Systems - Burns, Jed M.; Clark, Timothy; Williams, Craig M. (Journal of Organic Chemistry, 2021)
The course of the Barton-Kellogg (BK) reaction for alkyl- and aryl-substituted substrates has been investigated at the DLPNO-CCSD(T)/def2-TZVPP//omega B97X-D/def2-TZVPP level of theory, with results compared to available experimental kinetic data. Through comparison with the unsubstituted parent system, the preference for the formation of 1,3,4-dihydrothia-diazole over the isomeric 1,2,3-dihydrothia-diazole was observed to result from reduced steric repulsion in the relevant transition-state structure. Nitrogen extrusion [retro-(3 + 2)-cycloaddition] from the intermediate dihydrothiadiazole was found to be the rate-determining step. The barrier for this process was, however, significantly lower for aromatic substrates, which is consistent with the difficulty in isolating aryl-substituted dihydrothiadiazoles. The electronic structure of the transient thiocarbonyl ylide was also investigated, highlighting the contradictory results from wave-function theory- and density functional theory-based methods. Correlation of unrestricted natural orbital eigenvalues with previous experimental models suggested that the dipole intermediates possess low diradical character and are therefore considered to be closed-shell species. Exergonic conrotatory electrocyclization of the dipole led to sterically congested thiirane products, even for very bulky systems (di-t-butyl). These results complement the recent work of Mloston et al. Finally, DLPNO-CCSD(T)//omega B97X-D was found to be a reliable method for estimating the feasibility of the BK reaction, which should assist experimentalists in the selection of viable substrates.
CRIS-Team WoS Importer:2021-07-09